Revision of Molopsis Schatzmayr (Coleoptera: Carabidae: Pterostichini), with descriptions of four new species - Lohaj, Roman; Guéorguiev, Borislav; Dubault, Gérard; Lassalle, Bernard (Zootaxa, 2012)
The species belonging to the subgenus Molopsis Schatzmayr, 1943 of genus Tapinopterus Schaum, 1858 are revised. Thestudy is based on 372 specimens and includes, for each taxon, diagnosis, description (only for the new species), references,new distributional records and illustrations. Morphological characters of the male and female genitalia are widely used todelimit the separate species, the significance of some non-gonapophyseal genital structures of the females for the system-atics of Molopsis is explicitly emphasized. For the first time, the male genitalia of T. molopiformis, T. molopinus, T. wie-demanni, and T. rebellis, including also newly described species, as well as female genitalia of Molopsis are described andillustrated. All available type material is listed and represented by habitus photographs.As a result, 9 monotypic species of Molopsis are recognized. Tapinopterus rebellis (Chaudoir, 1868) and T. rebelliskumanensis (Reitter, 1884), formerly assigned to Molopsis are recognized as outgroup-taxa. The following new speciesare described: T. (Molopsis) aenigmaticus sp.nov. (Asian Turkey, „Armenia“ imprecise locality), T. (Molopsis) chaudoirisp.nov. (Asian Turkey, Bursa Villayet, Uludağ Mt., Sakarya (Adapazari) Villayet, Gökdağ Mt.), T. (Molopsis) oyukluensissp.nov. (Asian Turkey, Konya Villayet, Fasihan Pass), and T. (Molopsis) relegatus sp.nov. (Asian Turkey, Bolu Villayet,Mengen env., Dorukhan Pass). The following nomenclatural acts are also proposed: Tapinopterus (Molopsis) molopinus (Chaudoir, 1868) = Tapinopterus (Molopsis) dipojranus brussanus Straneo, 1984, syn.nov.; Tapinopterus (Molopsis)